Skywalkers : Mohawk ironworkers build the city - Weitzman, David, 1936- (Flash Point / Roaring Brook Press, 2010)
Narrative text and photographs examines Native American history and the development of structural engineering and architecture, focusing on Mohawk ironworkers.